Analysis of the prerequisites of the standartization of land management documentation - Avramchuk, B.; Kharytonenko, R.; Patiyuk, O.; Lashkevych, O. (Land Management, Cadastre and Land Monitoring, 2019)
The authors developed twelve land management projects for the allocation of land plots to individuals and submitted them for approval to the territorial body of the central body of executive power, which implements state policy in the field of land relations.The peculiarity of the study is that the developed projects are identical in terms of location of land (adjacent land users), purpose, soil, composition of land and restrictions and burdens on their use. However, the responses of the territorial body of the central executive body implementing state policy in the field of land relations to the consideration of each of these projects are different, despite the fact that the aforementioned land management projects were developed using the same methods, software and the same contractors.The lack of a unified system of standards for the development of land documentation and its constituent parts, as well as the criteria for reviewing and evaluating the compliance of such documentation with the territorial bodies of the central executive body implementing state policy in the field of land relations, is a key obstacle to a transparent land management process.This, in turn, creates the need to analyze the preconditions for standardization of documentation on land management and its components.Keywords: land management documentation, land management, land management project, standardization.